2020
DOI: 10.26508/lsa.202000744
|View full text |Cite
|
Sign up to set email alerts
|

An atlas of human proximal epididymis reveals cell-specific functions and distinct roles for CFTR

Abstract: Spermatozoa released from the testis are unable to fertilize an egg without a coordinated process of maturation in the lumen of the epididymis. Relatively little is known about the molecular events that integrate this critical progression along the male genital ducts in man. Here, we use single cell RNA-sequencing to construct an atlas of the human proximal epididymis. We find that the CFTR, which is pivotal in normal epididymis fluid transport, is most abundant in surface epithelial cells in the efferent duct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 76 publications
7
61
0
Order By: Relevance
“…Halo cells are considered intraepithelial immune cells of the epididymal duct, but the exact immunological function of these cells is currently still controversial. Several data indicate that halo cells belong to the mononuclear phagocyte system (MPS) [32,33], while others refer to halo cells as T lymphocytes [34]. However, showing high consistency to our results Serre and Robaire [35] showed that halo cells are positive for CD68, a macrophage-specific protein, and recently it was postulated that these cells belong to the MPS using RNA sequencing [32].…”
Section: Replication Is Linked To Mononuclear Cells Of the Respective Tissuessupporting
confidence: 82%
See 1 more Smart Citation
“…Halo cells are considered intraepithelial immune cells of the epididymal duct, but the exact immunological function of these cells is currently still controversial. Several data indicate that halo cells belong to the mononuclear phagocyte system (MPS) [32,33], while others refer to halo cells as T lymphocytes [34]. However, showing high consistency to our results Serre and Robaire [35] showed that halo cells are positive for CD68, a macrophage-specific protein, and recently it was postulated that these cells belong to the MPS using RNA sequencing [32].…”
Section: Replication Is Linked To Mononuclear Cells Of the Respective Tissuessupporting
confidence: 82%
“…Several data indicate that halo cells belong to the mononuclear phagocyte system (MPS) [32,33], while others refer to halo cells as T lymphocytes [34]. However, showing high consistency to our results Serre and Robaire [35] showed that halo cells are positive for CD68, a macrophage-specific protein, and recently it was postulated that these cells belong to the MPS using RNA sequencing [32]. More specifically, halo cells are suspected to contribute to the immunological part of the blood-epididymis barrier [35][36][37][38].…”
Section: Replication Is Linked To Mononuclear Cells Of the Respective Tissuesmentioning
confidence: 99%
“…7 Besides, structural proteins required for flagella formation and proteins involved in the energy metabolism are known to be associated with asthenozoospermia. [8][9][10] A more recent study has also suggested the involvement of non-coding RNAs and circular RNA in asthenozoospermia. 11 Despite these efforts, the etiology of asthenozoospermia remains far to be illustrated.…”
Section: Introductionmentioning
confidence: 99%
“…[10] While the epididymis is present in avian species, it is comparatively much shorter as compared to most mammals, 79 cm in the Japanese quail for example, with sperm transit completed in less than 24 h. [11][12][13] as over-expressing multiple antimicrobial peptides, including β defensins, as compared to other cell types. [30] Additionally, scRNA-seq analyses in the mouse model identified a sub-clustering of principal cells which exhibited stereocilia, non-motile cilia which aid in absorption and secretion, thus suggesting further examination of all cell types for the presence of subclusters in regards to gene expression. [31] The primary function of the clear cells is to regulate the acidic luminal pH via secretion of ATPases.…”
Section: Introduction To Epididymal Sperm Maturationmentioning
confidence: 99%
“…However; data from recent scRNA-seq analyses also observed similar roles identified in ionocytes, cells which contain multiple ion channels, suggesting the histological definition of a clear cell may also include this cell type. [30] The function of basal cells is relatively unknown compared to the other types, but studies suggest these may serve to support the bloodepididymis barrier as they line the basal surface of epididymal tubules. Evidence also indicates these cells exhibit high levels of membrane trafficking, with the secretion of cell adhesion molecules and potentially vesicles.…”
Section: Introduction To Epididymal Sperm Maturationmentioning
confidence: 99%